Does Islam require women to stay home? - Hasan, Md. Mahmudul (2020)
The precepts of hajj, rihlah, hijrah and hijab question the notion that the religion of Islam conditions women to be secluded and confined to private spheres. They invalidate any suggestion that it restricts women’s mobility and spatial freedom. If women choose to stay home in order to spend more time with their children rather than combining work and family, that is their right as well as a matter of necessity and a question of priority. For making the choice of staying home, often non-Muslim women are regarded as ‘devoted’ and Muslim women, as ‘oppressed’ or ‘submissive’ needing rescue from their religion and from their men. However, it is important to know that Islam does not allow spatial injustice based on gender and does not limit women’s freedom of movement.